Nationwide implementation of a multifaceted, tailored strategy to improve uptake of standardized structured reporting in oncological pathology: An effect and process evaluation. Issue 28 (1st October 2022) - Swillens, Julie; Voorham, Quirinus; Akkermans, Reinier P.; Nagtegaal, Iris D.; Hermens, Rosella
Abstract : 336 Background: Implementation strategies improve guideline adherence. Effect and process evaluations are conducted to provide insights into success or failure of implementation strategies. We conducted both evaluations to determine nationwide implementation of standardized structured reporting (SSR) in pathology, to facilitate optimal treatment decisions in oncology care. Methods: We conducted an interrupted time series analysis to evaluate the effect of a fully digital nationwide implementation strategy on SSR use in pathology laboratories. We further conducted a process evaluation to evaluate the exposure to the strategy elements, the experiences of the users with the implementation strategy and remaining barriers of SSR implementation. We also tested whether being exposed to a specific element of the strategy resulted in more increase of average SSR use. Results: There was a significant increase in average SSR use directly after the strategy introduction for reporting of gastrointestinal ( p =.018) and urological ( p =.003) oncological diagnoses. A significant increase was present for all oncological resections as a group ( p =.007). The "Feedback button", an option within the templates used for standardized structured reporting to provide feedback to the provider and one of the elements of the implementation strategy, was most frequently used by the SSR users and effectiveness results showed that it increased average SSR use after strategy introduction. Remaining barriers most related to rigidity, time consumption and content of SSR. Conclusions: Nationwide SSR implementation improved for specific tumor types and retrieval methods. Next step will be to further improve the use of SSR, and simultaneously, to further develop potential benefits of high SSR use, focusing on re-using discrete pathology data. In this way, we can eventually facilitate proper treatment decisions in oncology.